Corpus-based studies in language use, language learning, and language documentation - Newman, John, 1948-; Baayen, R. Harald; Rice, Sally, 1956- (Language and computers, 2011)
This volume consists of selected papers from the 2009 meeting of the American Association for Corpus Linguistics. The chapters cover aspects of language use (usage-based accounts of morphology/syntax of English and Tok Pisin), language learning (corpus-based learning of English, syntactic development observable in a Learner Corpus of English, "core" vocabulary items for learners of English) and language documentation (a new and innovative usage-based frequency dictionary of English, proposals to broaden the traditional understanding of a corpus in various directions, e.g., constructing a corpu.